Answer:
The first number: 14
The second number: 16
The third number: 18
Step-by-step explanation:
Equations
Let's assume:
x=the first even number.
x+2=the second even number
x+4=the third even number
The sum of all three is: x + x + 2 + x + 4
The condition states the sum decreased by 34 equals the first number:
x + x + 2 + x + 4 - 34 = x
Moving all the variables to the left side and the numbers to the right side:
x + x + 2 + x + 4 - 34 - x = 34 - 2 - 4
Simplifying:
2x = 28
Solving:
x = 28 / 2 = 14
The first number: 14
The second number: 16
The third number: 18